"Sea cucumber"-like Ti@MoO3 nanorod arrays as self-supported lithium ion battery anodes with enhanced rate capability and durability. Issue 45 (9th October 2015) - Zhao, Guangyu; Li, Changle; Zhang, Li; Lv, Jixian; Niu, Yanning; Du, Ying; Sun, Kening
Abstract : "Sea cucumber"-like Ti@MoO3 nanorod arrays show enhanced rate capability and excellent durability as self-supported lithium ion battery anodes. Abstract : MoO3 nanoparticles were electrodeposited on Ti nanorod arrays. The "sea cucumber"-like Ti@MoO3 nanorod arrays showed enhanced rate capability (300 mA h g −1 at 100 A g −1 ) and excellent durability (retaining 300 mA h g −1 after 1500 cycles at 20 A g −1 ) as self-supported Li ion battery anodes.